THE ANALYSIS METHODS DEVELOPMENT OF THE EFFECTIVENESS OF THE BASIC PRODUCTION ASSETS OF RAIL OPERATORS - Cherednychenko, M. S. (Science and Transport Progress, 2008)
A method of economic evaluation for the efficiency of using the capital production assets of railway transport operators is developed. The method allows calculating the optimum necessity in freight cars taking into account the financial and technological risks during transportations by both own cars and cars of inventory stock.